2021
DOI: 10.1371/journal.pone.0261361
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric, biochemical, and nutritional risk factors for osteoporosis in Korean adults based on a large cross-sectional study

Abstract: Background Osteoporosis a common bone disorder characterized by decreases in bone mass, tension, and strength. Although many previous studies worldwide have sought to identify the risk factors for osteoporosis, studies that simultaneously examine a variety of factors, such as biochemical, anthropometric and nutritional components, are very rare. Therefore, the objective of this study was to simultaneously examine the association of osteoporosis with biochemical profiles, anthropometric factors, and nutritional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
1
0
0
Order By: Relevance
“…Moreover, our study found that higher Hb and Hct levels were protective factors against osteoporosis. This concurs with other studies [ 54 , 55 , 56 ]. In fact, lower levels of Hb and Hct reflect an anemia status, which increases osteoclast activity [ 55 ].…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, our study found that higher Hb and Hct levels were protective factors against osteoporosis. This concurs with other studies [ 54 , 55 , 56 ]. In fact, lower levels of Hb and Hct reflect an anemia status, which increases osteoclast activity [ 55 ].…”
Section: Discussionsupporting
confidence: 94%